Incorporating students' voices in the 'Lesson Study' as a teacher-training and improvement strategy for inclusion / La incorporación de la voz del alumnado a la 'Lesson Study' como estrategia de formación docente y mejora para la inclusión. Issue 1 (2nd January 2018) - Simón, Cecilia; Echeita, Gerardo; Sandoval, Marta
Abstract: An experience of collaborative action research to improve teaching practices from an inclusive perspective is discussed. The aim of the project is to promote teaching practices for compulsory secondary education teachers that facilitate all students' learning and participation. We have used two strategies as catalysts of change. The first is student participation and the second is teacher collaboration in developing what is called the Lesson Study. Different phases in the action research are discussed, as are the dynamics used. The didactic experience focuses particularly on student participation. The results show the potential of the planning process to help student voices to be heard and taken into account as a way to improve teaching practice and reduce marginalization. Finally, we examine some lessons learned, including conditions and barriers that may limit these processes, as well as challenges.